In a cloud of dust - Fullerton, Alma (Pajama Press, 2015)
"Inspired by the many bicycle libraries that have opened all across Africa, In a cloud of dust is an uplifting example of how a simple opportunity can make a dramatic change in a child's life"--Page 4 of cover.